About the need for optical gear measurements using a beam diversion mechanism in order to obtain truthful surface texture parameters / Beurteilung der Notwendigkeit einer Strahlumlenkung für optische Zahnradmessungen zur Bestimmung korrekter Oberflächentexturkennwerte - Müller, Andreas; Hausotte, Tino (Technisches Messen)
The following article shows, that the optical characterisation of work piece surfaces with varying angles of inclination leads to different surface texture parameters. These results justify the development of a customised measurement setup using a optical beam diversion mechanism for the correct evaluation of gear wheel flank
Keywords: Surface texture parameters; focus variation; angle of incidence; gear wheel measurement